3-Aminopyrazolo[4, 3-c]pyridine-4, 6-dione as a precursor for novel pyrazolo[4, 5, 1-ij][1, 6]naphthyridines and pyrido[4', 3':3, 4]pyrazolo[1, 5-a]pyrimidines. Issue 13 (3rd July 2018) - Metwally, Nadia H.; Deeb, Emad A.
ABSTRACT: The versatile, 3-aminopyrazolo[4, 3-c]pyridine-4, 6-dione (2 ) was synthesized and allowed to react with aldehydes, aryldiazonium chlorides, chalcones and enaminones to afford regioselectively the novel pyrazolo[4, 3-c]pyridine derivatives4a-c, pyrazolo[4, 5, 1-ij][1, 6] naphthyridines9a-d and pyrido[4', 3':3, 4]pyrazlo[1, 5-a]pyrimidines19a-i . The structure of all the newly synthesized compounds was assigned from elemental analysis and spectral data. Also, the mechanistic aspects for the formation of the newly synthesized compounds is discussed. GRAPHICAL ABSTRACT: